Stomatal Dimorphism of Neodiplogaster acaloleptae (Diplogastromorpha: Diplogastridae). - Natsumi Kanzaki (PLoS ONE)
Several genera belonging to the nematode family Diplogastridae show characteristic dimorphism in their feeding structures; specifically, they have microbial feeding stenostomatous and predatory eurystomatous morphs. A diplogastrid satellite model species, Pristionchus pacificus, and its close relatives have become a model system for studying this phenotypic plasticity, with intensive physiological and structural studies having been undertaken. However, the many other species that are morphologically and phylogenetically divergent from P. pacificus have not been examined to date. In the present study, the detailed stomatal structure and induction of dimorphism in Neodiplogaster acaloleptae were examined. N. acaloleptae has a fungal feeding stenostomatous morph and a predatory eurystomatous morph. The predatory morph was induced by starvation, high population density, and co-culturing with its potential prey, Caenorhabditis elegans. The feeding behavior of the stenostomatous and eurystomatous morphs of N. acaloleptae was confirmed, demonstrating that 1) the stomatal and pharyngeal movements of the two morphs were basically identical, and 2) the stomatal elements were protracted to cut open the hyphae and/or prey to feed when a N. acaloleptae flips its dorsal movable tooth dorsally and tilts its subventral stegostomatal cylinder ventrally, forming a pair of scissors to cut the food source. The stoma morphology of N. acaloleptae with a single movable tooth and a long stoma is markedly different from that of Pristionchus, which has two movable teeth and a short stoma. It is, however, similar to that of Mononchoides, tentatively a sister to Neodiplogaster.